Plasma-assisted ALD to functionalize PET: towards new generation flexible gadgets. (2nd May 2017) - Fang, M; Zhang, H; Sang, L; Cao, H; Yang, L; Ostrikov, K; Levchenko, I; Chen, Q
Abstract: We report a novel, efficient, plasma-enabled technique to significantly enhance the protective barrier properties of alumina films deposited on thin polyethylene terephthalate (PET), which is a potential candidate for use in next-generation flexible gadgets and various portable equipment. Capacitively coupled oxygen plasma pretreatment was proposed and successfully tested to drastically reduce the water vapour transmission rate and water contact angle. The influence of the deposition temperature and in-chamber cooling of the prepared alumina layers on the protective characteristics of coated PET was also studied. We have found that higher deposition temperature improves the water vapour barrier performance of PET coated with atomic layer deposition alumina films. To keep the temperatures at a minimum, oxygen plasma could be efficiently employed to treat PET and thus ensure a strong interfacial interaction between the alumina and PET surfaces. With the assistance of the oxygen plasma treatment technique, alumina coating reduced the water vapour transmission rate of PET to less than 1 mg × m −2 × day −1 without a long post-process cooling. This technique may be suitable for application of virtually any ceramic films at low temperature onto various polymer substrates, which is urgently required for present-day flexible gadgets and other portable equipment including those working in aggressive environments.